Comparable Rates of Integrated Myofibrillar Protein Synthesis Between Endurance-Trained Master Athletes and Untrained Older Individuals - McKendry, James; Shad, Brandon J.; Smeuninx, Benoit; Oikawa, Sara Y.; Wallis, Gareth; Greig, Carolyn; Phillips, Stuart M.; Breen, Leigh (Frontiers in Physiology, 2019)
Background: An impaired muscle anabolic response to exercise and protein nutrition is thought to underpin age-related muscle loss, which may be exacerbated by aspects of biological ageing that may not be present in older individuals who have undertaken long-term high-level exercise training, or master athletes (MA). The aim of this study was to compare rested-state and exercise-induced rates of integrated myofibrillar protein synthesis (iMyoPS) and intracellular signaling in endurance trained MA and healthy age-matched untrained individuals (OC). Methods: In a parallel study design, iMyoPS rates were determined over 48 h in the rested-state and following a bout of unaccustomed resistance exercise (RE) in OC (n=8 males; 73.5 ± 3.3y) and endurance-trained MA (n=7 males; 68.9 ± 5.7y). Intramuscular anabolic signalling was also determined. During the iMyoPS measurement period, physical activity was monitored via accelerometry and dietary intake was controlled. Results: Anthropometrics, habitual activity and dietary intake were similar between groups. There was no difference in rested-state rates of iMyoPS between OC (1.47 ± 0.06%·day-1) and MA (1.46 ± 0.08%·day-1). RE significantly increased iMyoPS above rest in both OC (1.60 ± 0.08%·day-1, P<0.01) and MA (1.61 ± 0.08%·day-1, P<0.01), with no difference between groups. AktThr308 phosphorylation increased at 1h post-RE in OC (P<0.05), but not MA. No other between-group differences in intramuscular signalling were apparent at any time-point. Conclusions: While our sample size is limited, these data suggest that rested-state and RE-induced iMyoPS are indistinguishable between MA and OC. Importantly, the OC retain a capacity for RE-induced stimulation of skeletal muscle remodelling.